Gaslight [videorecording (DVD)] - Cukor, George, 1899-1983; Boyer, Charles, 1899-1978; Bergman, Ingrid, 1915-1982; Cotten, Joseph, 1905-1994; Whitty, May, Dame, 1865-1948; Lansbury, Angela, 1925-; Everest, Barbara, 1890-1968; Rameau, Emil, 1878-1957; Breon, Edmund, 1882-1951; Hobbes, Halliwell, 1877-1962; Stevenson, Tom, 1910-2004; Hamilton, Patrick, 1904 March 17-1962 (WB archive collection, 2011)
A susceptible young woman marries a suave, romantic man never suspecting that he is a murderous scoundrel, obsessed with finding the jewels hidden in her London home. She becomes the helpless victim as slowly, insidiously, he drives her to the brink of insanity.